Pengaruh Literasi Keuangan, Pengelolaan Keuangan, dan Inklusi Keuangan terhadap Kinerja UMKM di Kota Medan - Inda Kasih; Hendra Nazmi; Tri Kartika Yudha (https://jurnal.binamandiri.ac.id/, 2026)
This research aims to explain the influence of Financial Literacy, Financial Management, and Financial Inclusion on the Performance of MSMEs in Medan. The population in this study consists of 46,807 MSMEs in Medan. The sample was calculated using the Slovin formula, resulting in 100 respondents with the criteria of MSMEs in the culinary sector that have been operating for more than two years. The method used in this research is a quantitative method. Data collection techniques used a survey method in the form of a questionnaire. Data analysis used validity tests, reliability tests, classical assumption tests, multiple linear regression tests, F-tests, t-tests, and the coefficient of determination ( ) test using SPSS version 25. The test results show that Financial Literacy, Financial Management, and Financial Inclusion partially have a significant influence on MSME Performance. Simultaneously, Financial Literacy, Financial Management, and Financial Inclusion also have a positive and significant influence on the Performance of MSMEs in Medan with a significance value of 0,000.